Parameters of Lung function tests in healthy adult Bangladeshi population residing within Dhaka city: Lung function parameters in healthy adults of Dhaka - Mostofa, Rubyat; Akhter, Qazi Shamima; Rahman, Santunur (Journal of the Medical College for Women & Hospital, 2025)
Background: Lung functions are affected by age, gender, body built, ethnicity, environmental, socioeconomical, technical and other unidentified factors. Availability of appropriate reference value is necessary for interpretation of lung function tests and in assessment of respiratory disease. The standard value of pulmonary function test which is obtained from western population may not agree with Bangladeshi population as the two entirely different populations vary in ethnicity, body built, socioeconomic condition and environmental factors. Thus, attempt needs to be made to obtain values of these parameters more specific for the population of this region. Objective: The present study was carried out to find out values for lung function parameters of FVC, FEV1 and FEV1/FVC ratio of healthy adult Bangladeshi population residing in different parts of Dhaka city to contribute data towards obtaining reference value for these parameters for healthy Bangladeshi population in the near future. Materials and Method: A cross sectional study was conducted in the department of Physiology, Dhaka Medical College, Dhaka from July 2017 to June 2018. A total number of 150 male subjects and 150 female subjects were selected with age ranging from 18 to 45 years. The subjects were selected from different areas of Dhaka city on the basis of exclusion and inclusion criteria. The study parameters were estimated in the Department of Physiology, Dhaka Medical College, Dhaka by computerized digital autospirometer. Data were collected in a predesigned structured questionnaire form by the researcher herself. For statistical analysis Unpaired Student’s ‘t’ test and Pearson’s correlation coefficient (r) test were performed by using SPSS windows, version 16. p value <0.05 was accepted as level of significance. Results: In this study, values for lung function parameters of healthy adult Bangladeshi population residing within Dhaka city were estimated. Mean value for FVC, FEV1 and FEV1/FVC ratio were found 3L, 2.82L and 93% in male subjects and 2.43L, 2.21L and 93% in female subjects respectively. Conclusion: In this study we observed the values for lung function parameters of FVC, FEV1 and FEV1/FVC ratio for adult healthy Bangladeshi population residing in Dhaka city and may be considered as a visionary contributing step towards determining the parameters’ value for reference in this country. More such studies in other parts of Bangladesh needs to be carried out. Data from such studies may be compiled to eventually develop a reference value for the above parameters which would be more specific for healthy adult population of Bangladesh. J Med Coll Women Hosp.2025; 21 (2):71-77